Review Study of Physical and Cognitive Activities in Physics Active Learning: Model of Numbered Heads Together (NHT) - B., Ramadhan Valiant Gill S.; Sudarmi, Marmi; Kristiyanto, Wahyu Hari (International Journal of Active Learning, 2018)
This research aims to examine the proportion of physical activities and cognitive activities in the physics learning that using NHT as a learning model. The research is descriptive qualitative. There are three samples used in this research. Two of them are lesson plans. The other one is a video of physics learning that applicate NHT model. The result shows that in sample 1 which is RPP 1 shows that proportion of physical activities and cognitive activities is 6.6% and 93.4% respectively, then in sample 2 which is RPP 2 shows that physical activities and cognitive activities proportion is 5.5% and 94.5% respectively, and the third sample which is the video shows that physical activities and cognitive activities proportion is 13.3% and 86.7% respectively. Based on the considerable study of percentage that done in the RPP and the learning video shows that cognitive activities are more dominant than physical activities, this result is already accord with purpose of physics learning according to taxonomy bloom but this result also not accord with the basic idea of cooperative learning which is constructivism because in three sample student are not push to get the knowledge by their work. Based on that research finding it is suggested that in the learning activity that using NHT teacher use a drive questions so the cognitive activity in the learning can be accord with the target of basic idea from the NHT which is constructivism